Optimalisasi Program CSR PT Petrokimia Gresik Pada Penyaluran Bantuan Masjid, Musala, Pondok Pesantren, Dan Panti Asuhan Untuk Pemberdayaan Masyarakat Sekitar Perusahaan - Anessya Anggia Savitri; Yuniningsih Yuniningsih (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Corporate Social Responsibility (CSR) program, namely a company program whose implementation has influence or benefits, social and environmental responsibility for the community around the company to stakeholders. Research on community service aims to identify optimization of one of PT Petrokimia Gresik's Corporate Social Responsibility (CSR) Community Development unit programs, namely, the distribution of donations to mosques, prayer rooms, Islamic boarding schools, and orphanages to empower the community around the company. Assistance was provided in Gresik, Kebomas and Manyar sub-districts. The total funding assistance for 134 houses of worship and social institutions reached IDR 632,500,000. By using a qualitative descriptive method, because the research focus is to describe and provide an overview of the information on the object being studied. The research that has been done has shown that the Corporate Social Responsibility (CSR) program, namely, the distribution of donations to mosques, prayer rooms, Islamic boarding schools and orphanages has been running effectively. Because the beneficiary community feels helped and useful for their needs. This program is also aligned with Sustainable Development Goal 9, namely Industry, Innovation and Infrastructure.